Bronchiectasis in African children: disease burden, aetiology and clinical spectrum at a paediatric tertiary hospital in Cape Town, South Africa - Mapani, Muntanga-Mapani (Department of Paediatrics and Child Health, 2023)
Childhood bronchiectasis is a common cause of chronic lung disease globally, particularly in lower-middle-income countries (LMIC). Data from LMIC is lacking. We aimed to describe the disease burden, aetiology, and clinical spectrum of bronchiectasis in children attending a tertiary hospital in Cape Town, South Africa. Methods Data was collected by chart review of all patients 3 months to 15 years attending the respiratory clinic at red cross war memorial children's hospital between January – December 2019. We included children who had a diagnosis of bronchiectasis based on history of a recurrent (> 3 episodes/year) or persistent (> 4 weeks) wet cough, a clinical phenotype characterized by any of; exertion dyspnea, recurrent chest infections, growth failure, finger clubbing and chest deformity associated with radiographic features of bronchiectasis on plain chest radiography or HRCT reported by a paediatric radiologist. Patients with cystic fibrosis were excluded. Results Of 337 children seen during the study period, 58 (17.2%) had bronchiectasis that was diagnosed at a mean age of 34 months (SD 26). There were 32 (55.0%) female participants. The commonest causes of bronchiectasis were post-infectious (25, 43.1%), and underlying immunodeficiencies (19, 32.8%) including 16/58 (27.6%) who were HIV-infected and 3 (5.1 %) with primary immunodeficiency. Other causes included aspiration syndrome (8, 13.8 %) and anatomical abnormalities (4, 6.9%). Of the participants with post infectious bronchiectasis, tuberculosis was the commonest organism that was isolated (16, 64.0%) and commonest in children living with HIV (11/16, 68.8%). Cough was common (48, 82.8%) with wet cough being predominant (41, 85.4%), course crepitations accounted for 37 (63.8%), hyperinflation 24 (41.4%) finger clubbing 21 (36.2%), wheeze 16 (29.3%) and exertional dyspnea in 7 (12.0%). Conclusion: Bronchiectasis is a common cause of chronic lung disease in South African children mostly resulting from previous pneumonias, with tuberculosis being the commonest infective cause. The importance of identifying underlying treatable causes is highlighted.